(untitled) (Revista Iberoamericana de Bioética, 2024)
AI offers great benefits, but it can also cause harm, which should lead us to think ethically and legally. From ethical reflection, one conclusion is obvious: AI should not cause harm, and, on the other hand, if an AI system does cause harm, it will be necessary to establish a responsible party to compensate the victim for the harm caused. This responsibility will also encourage the manufacturing of safer and more reliable AI systems. Unfortunately, existing legislation does not address these problems, and new regulations are needed. The EU is addressing these issues by seeking to mitigate the evidentiary difficulty, and establishing that the manufacturer will be responsible for products that incorporate AI systems that do not have the security that would legitimately be expected.